2016
DOI: 10.1007/s00227-016-2859-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the growth and survival of the tropical vermetid gastropod Ceraesignum maximum is driven by size, habitat, and density

Abstract: with biomass was steeper for reefs where vermetid densities had been experimentally reduced. Survival was also greater on living coral Porites lobata (where coral growth covered longitudinal extensions of vermetid shells) relative to dead coral substrate (where vermetid shells extensions remained exposed). These data suggest little scope for regulation of vermetid population growth via direct density dependence in demographic rates. However, given that vermetids can kill corals, and vermetid survival probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Predation pressure is likely to be considerable within the shallow-water reef habitats where most vermetids are found ( Jones, Ferrell & Sale, 1991 ), with known vermetid predators including fish, sea stars, crabs, octopus and neogastropods ( e.g. , Menge et al., 1986 ; Osman, 1987 ; Calvo & Templado, 2005 ; Ramírez et al., 2013 ; Shima, Phillips & Osenberg, 2016 ; Brown et al., 2014 ; Shlesinger, Akkaynak & Loya, 2021 ). Even if not directly targeted as a prey item, sessile vermetids are also likely to be constantly exposed to grazing activities by parrotfish and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predation pressure is likely to be considerable within the shallow-water reef habitats where most vermetids are found ( Jones, Ferrell & Sale, 1991 ), with known vermetid predators including fish, sea stars, crabs, octopus and neogastropods ( e.g. , Menge et al., 1986 ; Osman, 1987 ; Calvo & Templado, 2005 ; Ramírez et al., 2013 ; Shima, Phillips & Osenberg, 2016 ; Brown et al., 2014 ; Shlesinger, Akkaynak & Loya, 2021 ). Even if not directly targeted as a prey item, sessile vermetids are also likely to be constantly exposed to grazing activities by parrotfish and others.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of vermetid predation are sparse, but main predators are known to include fish (such as pufferfish, triggerfish, and parrotfish), sea stars, crab, octopus, and neogastropods ( e.g. , Menge et al., 1986 ; Osman, 1987 ; Calvo & Templado, 2005 ; Ramírez et al., 2013 ; Shima, Phillips & Osenberg, 2016 ; Brown et al., 2014 ; Shlesinger, Akkaynak & Loya, 2021 ). In intertidal and reef environments with strong predation pressure by grazing and scraping fish, the defense strategy by members of some genera ( Dendropoma , Novastoa ) includes building strong low-lying shells, reducing the profile further by actively entrenching into the substratum by radula action, and closing the aperture with a large operculum that is held shut by the animal’s strong columellar muscle ( Golding et al., 2014 ; Schiaparelli et al., 2017 ; Bieler, 1983–2023, pers.…”
Section: Introductionmentioning
confidence: 99%
“…As recently summarized by Shima, Phillips & Osenberg (2016), vermetids can cause growth anomalies in corals and are known to substantially reduce coral growth (Colgan, 1985; Zvuloni, Armoza-Zvuloni & Loya, 2008; Shima, Osenberg & Stier, 2010; Stier et al, 2010; Shima, Phillips & Osenberg, 2013) and might be able to shift coral species composition in a region (Shima, Osenberg & Stier, 2010). Colgan (1985) suggested that the vermetid mucous feeding web can inhibit its coral host’s growth in four ways: by reducing water circulation, by attenuating light, by intercepting food, or by irritating the coral’s surface.…”
Section: Discussionmentioning
confidence: 99%